Health in ruins : the capitalist destruction of medical care at a Colombian maternity hospital - Abadía-Barrero, César (Experimental futures., 2022)
"In Health in Ruins César E. Abadía-Barrero chronicles the story of El Materno-Colombia's oldest maternity and neonatal health center and teaching hospital-over several decades as it faced constant threats of government shutdown. Using team-based and collaborative ethnography to analyze the social life of neoliberal health policy, Abadía-Barrero details the everyday dynamics around teaching, learning, and working in health care before, during, and after privatization. He argues that health care privatization not only is about defunding public hospitals; it also ruins rich traditions of medical care by denying or destroying ways of practicing medicine that challenge western medicine. Despite radical cuts in funding and a corrupt and malfunctioning privatized system, El Materno's professors, staff, and students continued to find ways to provide innovative, high-quality, and non-commodified health care. By tracking the violences, conflicts, hopes, and uncertainties that characterized the struggles to keep El Materno open, Abadía-Barrero demonstrates that any study of medical care needs to be embedded in larger political histories."--